Plan your career and take control of your future! - PAVELEA, Anișoara (2024)
The term career has different meanings for sociology, psychology, economics, andeducation scholars. For sociologists, careers have been studied in relationship to social mobilityand social stratification, occupations, status passages, power and control, or the influence of race,gender, ethnicity, origin, and education. For economics, careers are linked to income, activeworkforce, and unemployment rates, or retiring plans. For educators, they are relevant in thetransition from school to work, in relationship to educational choices and school curriculum. Forpublic policy, careers are linked to diversity, equity and inclusion, fair access to resources,reskilling and upskilling or lifelong learning. For psychologists, especially the organizational ones,patterns, trajectories, contingencies, transitions and turning points are studied, along with theaccumulation of cultural capital, and work relationships between employers and employeesfocusing on roles and procedures, leadership, reward systems and performance management,productivity, satisfaction, engagement, values, skills, wellbeing, and burnout. For careerpsychologists and counsellors, the focus is on individual traits, abilities, skills, motivations, values,interests, needs and the person – environment fit, the implementation of self-concept, career stagesand individual agency, social learning, information processing, planning, and decision making, orsense-making using narratives and metaphors.